The Value of Tolerance in the Narrative of the Civil Comic Kampung Sukaraya as a Media of Religious Moderation - Ni Nyoman Ayu Suciartini (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2023)
PurposeThe purpose of this study is to analyze the values of religious tolerance in comic narratives that can be used as a medium of religious moderation. MethodThis study uses a semiotic analysis method with a qualitative approach. Semiotic research is a method for analyzing and assigning meanings to the symbols of messages or texts. Results/FindingsThis study presents findings that from signs, images, and symbols combined with intrinsic elements in the form of plot, atmosphere, characterizations, and messages contained in these civil comic stories that present values of tolerance, mutual respect, helping others despite different beliefs and views, carry out religious obligations without harming humanity. ConclusionThe conclusion in this study is that the context of the story that is built in this comic is very closely related to real life in society, for example, regarding wisdom in dealing with hoax news, helping residents even though they have different beliefs or beliefs, respecting other people's opinions, not excluding a certain religion or teaching so that the idea that one religion is better than another, all the contexts discussed in the comic narration are presented to provide an understanding to the public about the importance of having a sense of tolerance to be able to accept every difference as a necessity and be able to live harmoniously side by side with all these differences.